Formulação multipotencial para modelos de degradação elástica: unificação teórica, proposta de novo modelo, implementação computacional e modelagem de estruturas de concreto - Samuel Silva Penna (2011)
This thesis presents a theoretical and computational framework for constitutive models based on elastic degradation. Classical models to deal with material's media degradation are addressed in the context of the theoretical and computational proposal. In addition, smeared cracking model's are reformulated, considering multiple uncoupled loading functions and a generalized degradation rule. To illustrate the potentiality of the created theoretical and computational framework, some damage models, founded in the literature, are implemented as well as a classical plasticity model. Also is proposed a new damage model with multiple loading functions. The created computational system takes advantage of the object-oriented programming paradigm, enabling to implement the proposal unifed theoretical framework, independently of the applied numerical method. However, only the Finite Element Method (FEM) is used in the validation of this unifed theory and the constitutive models inserted on it. Several application examples are presented, in order to illustrate the modeling possibilities provided by the constitutive models library gathered in this work. The new proposed damage model is validated by examples that compare their results with experimental results or obtained with other models, available in the literature.